2007
DOI: 10.1038/sj.ejcn.1602910
|View full text |Cite
|
Sign up to set email alerts
|

Dietary combination of soy with a probiotic or prebiotic food significantly reduces total and LDL cholesterol in mildly hypercholesterolaemic subjects

Abstract: Objective: We hypothesized that a dietary combination of soy with either a probiotic (yoghurt) or a prebiotic (resistant starch) would result in enhanced lipid-lowering effects compared with a control soy diet, possibly via improvements in isoflavone bioavailability. Subjects: Mildly hypercholesterolaemic subjects (men and post-menopausal women) older than 45 years were recruited via the local media. Thirty-six subjects commenced the study; five withdrew. Results: Soy þ probiotic significantly decreased total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 39 publications
(47 reference statements)
3
36
0
10
Order By: Relevance
“…A number of recent studies have assessed the effect of equol status on the cholesterol-lowering potential of soy, with mixed results (3,(21)(22)(23)(24)(25). Two studies tested the hypothesis that increased colonic microbial activity might increase equol synthesis and so potentiate the action of soy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have assessed the effect of equol status on the cholesterol-lowering potential of soy, with mixed results (3,(21)(22)(23)(24)(25). Two studies tested the hypothesis that increased colonic microbial activity might increase equol synthesis and so potentiate the action of soy.…”
Section: Discussionmentioning
confidence: 99%
“…A further study that used a similar probiotic approach, but with the probiotic given as yogurt containing 10 8 colony forming units of each of Lactobacillus acidophilus, Bifidobacterium bifidus, and Lactobacillus GG per 100-g serving, showed a greater reduction in cholesterol on soy in those receiving the probiotic supplement (25) and a more consistent effect with both greater total cholesterol and LDL-cholesterol reductions with soy when a resistant starch supplement (bread containing a total of 16-20 g resistant starch) was provided to increase colonic microbial fermentation (prebiotic) (25). In our study, the subgroup who received prebiotic (oligofructose-enriched inulin) showed a potentiation of the soy cholesterol-lowering effect supporting the possible use of coadministration of a prebiotic with soy (10).…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia is one of the most significant risk factor for the cardio-vascular diseases. It has been determined that various probiotic species decrease the serum cholesterol levels in human (Larkin et al, 2009), experimental animals (Park et al, 2007) or farm animals (Özcan et al, 2003;Strompfova et al, 2006). However hypocholesterolemic effect of probiotics depends on the species of the bacteria.…”
Section: The Effects Of Probiotics On Cholesterol Absorptionmentioning
confidence: 99%
“…A soja representa uma série de vantagens em relação às outras fontes de proteína vegetal. Possuindo um elevado teor de proteínas (38% a 42%) de excelente qualidade e baixo custo, como também bom teor de isoflavonas, que auxiliam na redução do colesterol sanguíneo (MANDARINO & PANIZZI 2001;MANDARINO et al, 2002;LARKIN et al, 2009). Segundo PAES, (1994) a elevada relação polisaturados/saturados, à ausência de colesteral no óleo, à presença do ácido graxo linoleico, aliado à ação redutora de colesterol da proteína e das fibras.…”
Section: Na Redução De Doenças Cardíacasunclassified